2007
DOI: 10.1037/0736-9735.24.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamics of postpartum depression.

Abstract: Although there are numerous articles and books about postpartum depression, few are psychoanalytically informed, and the psychodynamics of women suffering from postpartum depression are overlooked in most of these publications. Psychoanalytic reports concerning postpartum depression are few, but clinical experience and the literature suggest that a triad of three common, specific emotional conflicts is typical of many women who develop postpartum depression. For simplicity, these are dependency conflicts, ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 47 publications
2
65
2
2
Order By: Relevance
“…Krzyżanowska-Zbucka [15] included psychosocial factors, such as lone motherhood and bad relationships in the family, into the group of risk factors for postpartum depression, similar to Jaeschke et al [13] and IwanowiczPalus et al [18], suggested careful observation of women who declared they would bring up their child alone. Snow [4] and Rokach [2] observed that a bad marriage constitutes a risk factor for the prevalence of mental disorders during the postpartum period, which was also stressed by Blum [37]. However, Reroń et al [17], did not indicate marital status as a factor that could affect the prevalence of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krzyżanowska-Zbucka [15] included psychosocial factors, such as lone motherhood and bad relationships in the family, into the group of risk factors for postpartum depression, similar to Jaeschke et al [13] and IwanowiczPalus et al [18], suggested careful observation of women who declared they would bring up their child alone. Snow [4] and Rokach [2] observed that a bad marriage constitutes a risk factor for the prevalence of mental disorders during the postpartum period, which was also stressed by Blum [37]. However, Reroń et al [17], did not indicate marital status as a factor that could affect the prevalence of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Chrzan-Dętkoś et al [19], showed that women who received care from their mothers during childhood had lower EPDS scores. Similarly, Blum [37] noted that women who demonstrated symptoms of postpartum depression were more likely to negatively assess the quality of care exercised over them by their mothers. Blum also pointed out that lack of adequate paternal care during childhood can have a similar effect on the prevalence of depressive disorders after giving birth.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Blum's assertion, a theoretically derived extensive empirical psychoanalytic database exists which confirms and extends Blum's analysis of the core dynamics involved in this disorder. This recent research derives primarily from the comprehensive theoretical framework proposed by Blatt (1974Blatt ( , 2004Blatt ( , 2006Blatt ( , 2008 on the psychodynamics of depression that are part of a broad theory of normal and pathological personality development which Blum (2007), in his otherwise thorough search of the literature, seems to have overlooked. The authors close with reflections on how psychoanalysis and psychodynamically inspired research might increasingly influence mainstream clinical practice and research.…”
mentioning
confidence: 99%
“…De facto, tal como afirma Blum (2007), o nascimento de um filho e a emergência da parentalidade são eventos que implicam uma reactivação do vivido de perda dos objectos primitivos, principalmente quando no passado não foram elaborados, transformando-se em manifestações directas e indirectas em relação ao filho. Este acordar das vivencias e conflitos anteriores acontece com ambos os pais e determina a forma como se adaptam ao bebé.…”
Section: Discussionunclassified